Immediate Effect of Self-Thai Foot Massage (STFM) on Balance and Ankle Joint Proprioception in Type II Diabetic Patients with Peripheral Neuropathy (DPN): A Single-Blind Randomized Controlled Trial - Saw Mya Soe; Wanpen, Sawitri; Thaweewannakit, Thiwabhorn; Peungsuwan, Punnee; Chatchawan, Uraiwan (Asia-Pacific Journal of Science and Technology, 2025)
Standard treatments for patients with type 2 diabetes (T2DM) and peripheral neuropathy (DPN) typically include foot care and exercise programs. Self-Thai Foot Massage has been proposed as an alternative therapy for managing this condition. This study investigated the immediate effects of the single intervention of Self-Thai Foot Massage on balance and proprioception of the ankle joint in T2DM with DPN. Ninety patients were recruited and randomly assigned to either the experimental group (EG), receiving Self-Thai Foot Massage and Standard Foot Care, or the comparable group (CG), receiving only Standard Foot Care. Both groups received a single 50-minute treatment. Balance was assessed using the Mini-Balance Evaluation Systems Test (MBT), ankle joint proprioception was measured using the Ankle Joint Proprioception (JPS) test, foot sensation was evaluated using the Semmes-Weinstein Monofilament Test (SWMT), and the active/passive range of motion of the ankle was measured using the Kinovea program, both before and immediately after a single treatment. The independent t-tests and Two-sample Mann-Whitney tests were used to compare post-treatment data between treatment groups. The EG and CG groups showed significant improvements in all outcome measures from baseline to immediately after the first treatment (p<0.05). The EG group demonstrated greater improvements than the CG group in almost all variables (p<0.05), except for active ankle range of motion in dorsiflexion on the left side. This study highlights the potential benefits of Self-Thai Foot Massage for immediate improvements in balance and proprioception of ankle joint, foot sensation, and ankle range of motion among these patients.